GLP-1 Mediates Regulation of Colonic ACE2 Expression by the Bile Acid Receptor GPBAR1 in Inflammation - Michele Biagioli; Silvia Marchianò; Rosalinda Roselli; Cristina Di Giorgio; Rachele Bellini; Martina Bordoni; Eleonora Distrutti; Bruno Catalanotti; Angela Zampella; Luigina Graziosi; Annibale Donini; Stefano Fiorucci (Cells, 2022)
Background & Aims: ACE2, a carboxypeptidase that generates Ang-(1-7) from Ang II, is highly expressed in the lung, small intestine and colon. GPBAR1, is a G protein bile acid receptor that promotes the release of the insulinotropic factor glucagon-like peptide (GLP)-1 and attenuates intestinal inflammation. Methods: We investigated the expression of ACE2, GLP-1 and GPBAR1 in two cohorts of Crohn’s disease (CD) patients and three mouse models of colitis and Gpbar1−/− mice. Activation of GPBAR1 in these models and in vitro was achieved by BAR501, a selective GPBAR1 agonist. Results: In IBD patients, ACE2 mRNA expression was regulated in a site-specific manner in response to inflammation. While expression of ileal ACE2 mRNA was reduced, the colon expression was induced. Colon expression of ACE2 mRNA in IBD correlated with expression of TNF-α and GPBAR1. A positive correlation occurred between GCG and GPBAR1 in human samples and animal models of colitis. In these models, ACE2 mRNA expression was further upregulated by GPABR1 agonism and reversed by exendin-3, a GLP-1 receptor antagonist. In in vitro studies, liraglutide, a GLP-1 analogue, increased the expression of ACE2 in colon epithelial cells/macrophages co-cultures. Conclusions: ACE2 mRNA expression in the colon of IBD patients and rodent models of colitis is regulated in a TNF-α- and GLP-1-dependent manner. We have identified a GPBAR1/GLP-1 mechanism as a positive modulator of ACE2.